Вплив кольору на споживчий вибір - Задорожна, В. К. (ХНУРЕ, 2023)
The article presents an overview of determining the impact of product color on consumer choice. The characteristics of the main influencing factors are given. The effect of color on a person is considered: it affects all his physiological systems, activating or suppressing their activity, creates a certain emotional mood due to associative imagination, has a biological innate preference for colors depending on age.
Keywords: колір